Psychometric properties and normative data of the childhood trauma questionnaire-short form in Chinese adolescents - Peng, Chang; Cheng, Junhan; Rong, Fajuan; Wang, Yan; Yu, Yizhen (Frontiers in Psychology, 2023)
Background: The Childhood Trauma Questionnaire-Short Form (CTQ-SF) is a widely utilized instrument of childhood maltreatment (CM). However, psychometric properties and normative data of the CTQ-SF for Chinese adolescents are still unknown. Objective: To examine psychometric properties and normative data of Chinese version CTQ-SF in a nationally representative sample of Chinese adolescents, including internal consistency reliability, test-retest reliability, structural validity, and convergent validity. Method: A total of 20,951 adolescents aged 12 to 18 years were recruited from five provinces across China. Item analysis was used for 25 clinical items of the CTQ-SF. Confirmatory factor analysis was performed to examine fit indices of the factor structure. The Adverse Childhood Experiences Scale (ACEs) was used to evaluate convergent validity. The percentile ranks for scores of the CTQ-SF and each subscales were presented. Results: According to the results of three methods in Item analysis, Item 4 should be dropped. The remaining 24 clinical items achieved satisfactory fits in an alternative four-factor model. The alternative CTQ-SF showed acceptable internal consistency and the Cronbach’s α of the four subscales was 0.824 (Neglect), 0.755 (Sexual Abuse), 0.713 (Physical Abuse), and 0.666 (Emotional Abuse), respectively. Besides, test-retest reliability and convergent validity of the alternative CTQ-SF were also acceptable. Conclusion: The alternative four-factor model CTQ-SF exhibits good reliability and validity among Chinese adolescents. Additionally, the normative information of the CTQ-SF could provide practical support for determining severity of different subtypes of CM.